2016
DOI: 10.1590/0001-3765201620150130
|View full text |Cite
|
Sign up to set email alerts
|

Hourly interaction between wind speed and energy fluxes in Brazilian Wetlands - Mato Grosso - Brazil

Abstract: Matter and energy flux dynamics of wetlands are important to understand environmental processes that govern biosphere-atmosphere interactions across ecosystems. This study presents analyses about hourly interaction between wind speed and energy fluxes in Brazilian Wetlands -Mato Grosso -Brazil. This study was conducted in Private Reserve of Natural Heritage (PRNH SESC, 16º39'50''S; 56º47'50''W) in Brazilian Wetland. According to Curado et al. (2012), the wet season occurs between the months of January and Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The climate in the study area showed a distinct seasonal variation (Figure 2). The dry season, which was defined as the period with a rainfall depth lower than 100 mm/month [4,54,55], occurred from April to October, and approximately 25% of the rainfall was recorded during this period (Figure 2F). Mean yearly accumulated rainfall (±sd) was 941 ± 297 mm during the study period, which is 34% lower than the expected rainfall for this region.…”
Section: Seasonal Variation In Micrometeorological Conditionmentioning
confidence: 99%
“…The climate in the study area showed a distinct seasonal variation (Figure 2). The dry season, which was defined as the period with a rainfall depth lower than 100 mm/month [4,54,55], occurred from April to October, and approximately 25% of the rainfall was recorded during this period (Figure 2F). Mean yearly accumulated rainfall (±sd) was 941 ± 297 mm during the study period, which is 34% lower than the expected rainfall for this region.…”
Section: Seasonal Variation In Micrometeorological Conditionmentioning
confidence: 99%
“…However, the spatial distribution and temporal variation of rainfall (Curado et al, 2016), as well as duration of droughts (Rodrigues et al, 2016a), can have a profound impact on the dynamics of energy exchange by affecting the partitioning of energy between sensible and latent heat fluxes (Vourlitis et al, 2008;Rocha et al, 2009;Rodrigues et al, 2013;. Because our current knowledge of the climate system is still insufficient to solve some of the divergent predictions about this topic, it is important to improve the understanding of mechanisms of vegetation-climate interaction in forested regions such as the Amazon (Gonçalves et al, 2013), whose seasonal patterns of certain biophysical and climatic parameters show complex interactions Rodrigues et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…2). We considered the dry season as the period with a rainfall depth lower than 100 mm/month (Hutyra et al 2005;Rodrigues et al 2014Rodrigues et al , 2016a. The dry season was defined from April to October, with approximately 25% of the recorded rainfall during the study period (Fig.…”
Section: Seasonal Variation In Micrometeorological Conditionmentioning
confidence: 99%